HOST MODULATION-A NEW WAVE IN THE PHARMACOTHERAPY OF PERIODONTITIS. - SHOBITHA MURUGAVEL; DR.RADHIKA ARJUNKUMAR (International Journal of Pharma and Bio Sciences, 2015)
Periodontitis is a polymicrobial infectious disease of multifactorial origin. Plaque biofilm associated host responses are involved in the pathogenesis of periodontitis. In periodontal diseases, bacteria trigger inflammatory host responses, which along with the direct destructive effects of the bacteria, cause most of the tissue destruction. Host modulation therapy aims to reduce tissue destruction and stabilize or regenerate the periodontium by modifying host responses. The role of host modulation therapy in the inhibition of these inflammatory mediators and the potential application of host modulation as a therapeutic intervention for the management of periodontal disease has been discussed in this review.